Management of ventral hernias: treatment results based on the developed algorithm - Ioffe, O. Y.; Tarasiuk, T. V.; Kryvopustov, M. S.; Stetsenko, O. P. (General Surgery, 2024)
The surgical treatment of anterior abdominal wall hernias is one of the most common procedures in elective surgery. However, the rate of laparoscopic hernioplasty is lower when compared to open methods. Experience in treating large ventral hernias (і 10 cm) using minimally invasive techniques is limited due to the inability to compare the edges of the hernial defect without component separation. Objective — to develop an algorithm for choosing a surgical treatment method for patients with ventral hernias and to evaluate the results of treatment. Materials and methods. A prospective multicenter study was conducted, which included 534 patients with ventral hernias of various sizes. All patients were treated from September 2011 to November 2024. Preoperatively, patients with hernias ≥10 cm were injected with 100 Units of botulinum toxin type A (BTA) into the muscles of the anterior abdominal wall. The mean age of the patients was 56.49±14.59 years, with 307 (57.5%) women and 227 (42.5%) men. All patients underwent hernia surgery using laparoscopic and open hernioplasty methods according to the developed algorithm. Results. The algorithm classified patients into three groups based on their hernia size: group 1 — patients with hernias <4 cm wide (n=269; 50.4%), group 2 — with a size of 4—10 cm (n=173; 32.4%), and group 3 — with a size of ≥10 cm (n=92; 17.2%). The mesh was placed intraperitoneally during laparoscopic hernia repair. In all three groups, laparoscopic hernioplasty demonstrated a significantly lower rate of complications and length of hospital stay compared to open procedures (p <0.01). Seromas were among the most common complications in all three groups in our study (n=19; 7.1% vs n=26; 15.0% vs n=14; 50%), and their frequency increased with hernia defect size. In group 3, among patients with large hernias, BTA administration allowed for the reduction of the aponeurosis defect to ≤10 cm in size in 89.4% of cases and the performance of laparoscopic surgery in patients who agreed to it. The recurrence rate after laparoscopic surgery was 0.8%, while after open surgery, it was 1.1%. Conclusions. The use of the algorithm for selecting the hernioplasty method allows implementing a personalized approach to the surgical treatment of patients with ventral hernias. Laparoscopic hernioplasty with intraperitoneal mesh placement demonstrates significantly better results compared to open methods of hernia repair in terms of length of hospital stay and complication rate (p <0.01). The use of BTA for hernias ≥10 cm in the preoperative period makes it possible to perform hernioplasty using laparoscopic techniques and minimize surgical trauma in case the patient refuses laparoscopy.